Determination of yearly performance and degradation rate of electrical parameters of amorphous silicon photovoltaic module in Minna, Nigeria - Samuel Oluwatobi, Matthew; Joel Aghaegbunam, Ezenwora; Julia Ofure, Eichie; SaliuOlakanmi, Alilu; Aliyu, Ahmadu (International Journal of Physical Research, 2022)
There is need for accurate knowledge of degradation rate and lifespan of photovoltaic (PV) module in every location for an effective solar PV power system. Outdoor degradation analysis was carried out on amorphous silicon PV module rated 10 W using CR1000 software-based Data Acquisition System (DAS). The PV module under test and meteorological Sensors were installed on a metal support structure at the same test plane. The data monitoring was from 09:00 to 18:00 hours each day continuously for a period of four years, from December 2014 to November 2018. Annual yearly averages of the performance variables were carried out to ascertain the degradation rate and lifespan of the module. The module performance for the four years of study was compared with Standard Test Condition (STC) specifications. The maximum power achieved at 1000W/m2 for the four years of study were 0.652W, 2.186W, 2.078W, and 1.812W representing 6.52%, 21.86%, 20.78% and 18.12%of the manufacturerâ€™s 10W specification. Module efficiency at 1000W/m2 for the four years of study is 2.25%, 7.56%, 7.19%, and 6.27% respectively as against the manufacturers STC specification of 33%. Accordingly, Module Performance Ratios for the PV module investigated were 0.07, 0.23, 0.22 and 0.19 respectively. For the Rate of Degradation (RoD), it was observed that Open-Circuit voltage (Voc), Short-Circuit Current (Isc), Power-Output (P), Maximum Power (Pmax), had an average yearly degradation rate of 0.73V, 0.010A, 0.040W, 0.050W respectively for the four years of study. To also determine the lifespan of the module, an empirically determined statistical model given as YEAR = 3.36 - 0.237 Voc (v) - 71.5 Isc (A) + 8.07 Power (W) was fitted to the observed data to predict the lifetime of the module at any given year.Â